PENGERINGAN ALAMI DAN BUATAN SEPULUH JENIS KAYU NUSA TENGGARA BARAT (Air drying and kiln drying properties of 10 wood species from Nusa Tenggara Barat) - Efrida Basri; Syarif Hidayat (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
This report presents result of a study on air drying properties and kiln drying schedule of ten wood species from Nusa Tenggara Barat. the study was carried out based On data from quick drying test. The result shows that, the quality of almost all of the species dried using air drying method are inferior compared with that obtained from kiln drying. the ten wood species used in the study can be grouped into four drying schedules, ringin, kabaukafa, sabaha and niu can be grouped into schedules 1 (easy to dry), katowi and kencari schedule 2, whereas red monggo and konca schedule 3, and mongo schedule 4 (difficult to dry).